Interconnected network‐like single crystalline bimetallic carbonate hydroxide nanowires for high performance hybrid supercapacitors. (7th October 2020) - Sivakumar, Periyasamy; Jana, Milan; Nakhanivej, Puritut; Jung, Min Gyu; Raj, Chellam Justin; Park, Ho Seok
Summary: The one‐dimensional (1D) nanoarchitectures are attractive toward energy storage electrode materials because of their large available surface area, a short and efficient pathway for ion/electron transport, structural stability, and highly exposed electrochemically active sites. Herein, we develop the bimetallic single crystalline nickel cobalt carbonate hydroxide (NiCoCO3 (OH)2 ) nanowires for the high capacitance electrode of hybrid supercapacitor (HSC). This unique NiCoCO3 (OH)2 nanowire electrode reveals a maximum specific capacitance value of 1948 F g −1 at 1 A g −1 with a high rate capacitance of 859 F g −1 even at 30 A g −1, which is a considerably higher value than the monometallic nickel carbonate hydroxide (1159 F g −1 ) and cobalt carbonate hydroxide (859 F g −1 ), respectively. These results are attributed to the presence of abundant redox‐active sites of multivalent Ni and Co and an easy charge transport pathway of NiCoCO3 (OH)2 nanowire. The as‐designed HSC full cells, configuring NiCoCO3 (OH)2 nanowire and activated carbon as a positive and native electrodes, respectively, deliver energy and power densities of 56.56 W h kg −1 and 44.81 kW kg −1 . Moreover, the HSC cells exhibit prominent cycling stability of 91.4% for 12 000 charge‐discharge cycles in 6 M KOH aqueous electrolyte. Abstract : Interconnected network‐like single crystalline bimetallic carbonate hydroxide nanowires for high performance hybrid supercapacitors